Diversidade química e atividades farmacológicas da espécie Justicia aequilabris - Silva, Joanda Paolla Raimundo e (2022)
Plant species show a great variability of secondary metabolites, which represent an important source of pharmacologically active molecules. Species of the genus Justicia have already offered the scientific community numerous bioactive molecules, but species such as Justicia aequilabris (Nees) Lindau, a native and endemic plant in Northeast Brazil, did not have phytochemical and pharmacological studies. Thus, the objective of this work is to investigate the chemical and pharmacological profile of J. aequilabris. The ethanolic extract was obtained from the aerial parts of the species, which was partitioned and the phases obtained analyzed by LC-MS and molecular networks. These tools indicated that the ethyl acetate phase had the greatest chemical diversity, so this phase was fractionated and the subfractions obtained were analyzed by NMR, with the unpublished compounds being elucidated, aequilabrine A (1), B (2) and C (3), and identify the molecules, lariciresinol-4′-O-β-glycoside (4), allantoin (5) and roseoside (6), secoisolariciresinol (7), pinoresinol-4-O-β-D-glycoside (8), epipinoresinol-4-O-β-D-glycoside (9), pinoresinol-4-O-β-D-apiosyl-(1→2)-β-Dglycoside (10). Through LC-EMn analysis of the extract, 22 compounds were dereplicated, these being lignans, flavonoids and phenolic acids. By molecular docking compounds 1-3 showed agonist activity at the glucocorticoid receptor. Therefore, these compounds were directed to in vitro analyses. Molecules 1 (IC50 = 9.1 μM) and 2 (7.3 μM) showed significant inhibitory activity against nitric oxide production, and a maximum inhibition rate of IL-1β production with values of 23.5% (1) , 27.3% (2) and 32.5% (3). Data from in silico and in vitro analyzes suggest that anti-inflammatory activity is related to substitution at C9 and C-9'.By virtual screening, compounds 7-10 were selected for in vitro analysis of the leshmanicidal activity against the promastigote forms of L. major and L. braziliensis, compounds 7 (IC50 = 9.28 μM) and 9 (5.39 μM) showed prominent activity against L. braziliensis. The use of tools such as the molecular network and molecular docking was essential in prioritizing the isolation of the compound of interest and targeting the pharmacological analysis of the molecules, the lignans described in the work showed potential anti-inflammatory and leshmanicidal activity.